Prevalence of parafunctional habits and temporomandibular dysfunction symptoms in patients attending a tertiary headache clinic Prevalência de hábitos parafuncionais e de sintomas de disfunção temporomandibular em pacientes atendidos em um ambulatório terciário de cefaléias - Yára Dadalti Fragoso; Heloísa Helena Carvalho Alves; Sidney Oliveira Garcia; Alessandro Finkelsztejn (Arquivos de Neuro-Psiquiatria)
OBJETIVE: To investigate the most prevalent forms of headache in a tertiary outpatient service, and to assess the frequency of associated parafunctional habits and temporomandibular dysfunction symptoms (TMD). METHOD: All new patients referred to the Headache Outpatient Service in UNIMES during 2008 were prospectively assessed by the neurologist and the dental surgeon. RESULTS: Eighty new patients were assessed; chronic migraine and episodic migraine without aura were the most prevalent conditions, accounting for 66.3% of all cases. There was significantly higher use of analgesics/days for the chronic migraine patients. The prevalence of parafunctional habits was 47.5% and the prevalence of TMD symptoms was 35%. CONCLUSION: The high prevalence of primary headaches, parafunctional habits and TMD symptoms and the inadequate use of analgesic drugs suggest that primary healthcare units need further training in the field of headache and orofacial pain. OBJETIVO: Investigar as formas prevalentes de cefaléia em um ambulatório terciário e analisar a frequência de hábitos parafuncionais e de sintomas de disfunção temporomandibular (DTM) associados. MÉTODO: Todos os pacientes novos encaminhados ao Serviço de Cefaléias da UNIMES durante 2008 foram avaliados de forma prospectiva pelo neurologista e pelo cirurgião dentista. RESULTADOS: Oitenta pacientes novos foram avaliados; enxaqueca crônica e enxaqueca episódica sem aura foram as condições mais prevalentes, perfazendo 66,3% de todos os casos. Houve uso significativamente alto de analgésicos/dias pelos pacientes com enxaqueca crônica. A prevalência de hábitos parafuncionais foi 47,5% e a prevalência de sintomas de DTM foi 35%. CONCLUSÃO: A alta prevalência de cefaléias primárias, hábitos parafuncionais, sintomas de DTM e o uso inadequado de drogas analgésicas sugerem que as unidades básicas de saúde necessitam maior treinamento no campo da cefaléia e da dor orofacial.